Methionine PET Might Be Reliable for the Detection of Low M-Protein–Producing Myelomas. (November 2017) - Imataki, Osamu; Uchida, Shumpei; Yokokura, Shigeyuki; Uemura, Makiko; Kadowaki, Norimitsu
Abstract : Abstract: 11 C-methionine (MET) positron emission tomography (PET) is more sensitive than 18 F-fluorodeoxyglucose (FDG)–PET for detecting myeloma lesion. Many clinical studies support this evidence mainly for multiple myeloma cases of IgG or IgA subtypes. However, this is not confirmed for low monoclonal protein-producing myelomas, such as IgD, IgE, and nonsecretory type. We encountered a 71-year-old man with IgD λ-type myeloma. In this patient, FDG-PET did not reveal any abnormal uptake lesions, whereas MET-PET revealed diffuse bone marrow uptake that relieved after initial chemotherapy. We speculate that the determinants for high serological activity of protein metabolism are transporter system activity or proliferation index.